2007
DOI: 10.1002/cm.20208
|View full text |Cite
|
Sign up to set email alerts
|

The Drosophila CLASP homologue, Mast/Orbit regulates the dynamic behaviour of interphase microtubules by promoting the pause state

Abstract: An important group of microtubule associated proteins are the plus-end tracking proteins which includes the Mast/Orbit/CLASPs family amongst others. Several of these proteins have important functions during interphase and mitosis in the modulation of the dynamic properties of microtubules, however, the precise mechanism remains to be elucidated. To investigate the role of Mast in the regulation of microtubule behaviour during interphase, we used RNAi in Drosophila S2 culture cells stably expressing GFP-alpha-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
54
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(66 citation statements)
references
References 63 publications
(102 reference statements)
12
54
0
Order By: Relevance
“…Msps interacts with CLASP in both the genetic and proteomic screens, and it antagonizes CLASP and Abl signaling. The antagonism seen between Msps and CLASP in the Drosophila retina is consistent with cell culture studies, which have shown that CLASP regulates MT dynamics by specifically promoting the pause state (Sousa et al 2007) whereas Mspsfamily proteins function as MT antipause factors (Brittle and Ohkura 2005). More specifically, CLASPs have MT-stabilizing effects (Drabek et al 2006), and depleting cells of CLASP protein results in highly dynamic, constantly growing or shrinking MTs (Sousa et al 2007).…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Msps interacts with CLASP in both the genetic and proteomic screens, and it antagonizes CLASP and Abl signaling. The antagonism seen between Msps and CLASP in the Drosophila retina is consistent with cell culture studies, which have shown that CLASP regulates MT dynamics by specifically promoting the pause state (Sousa et al 2007) whereas Mspsfamily proteins function as MT antipause factors (Brittle and Ohkura 2005). More specifically, CLASPs have MT-stabilizing effects (Drabek et al 2006), and depleting cells of CLASP protein results in highly dynamic, constantly growing or shrinking MTs (Sousa et al 2007).…”
Section: Discussionsupporting
confidence: 80%
“…The antagonism seen between Msps and CLASP in the Drosophila retina is consistent with cell culture studies, which have shown that CLASP regulates MT dynamics by specifically promoting the pause state (Sousa et al 2007) whereas Mspsfamily proteins function as MT antipause factors (Brittle and Ohkura 2005). More specifically, CLASPs have MT-stabilizing effects (Drabek et al 2006), and depleting cells of CLASP protein results in highly dynamic, constantly growing or shrinking MTs (Sousa et al 2007). Alternatively, Msps family members can have the opposite effect (Popov and Karsenti 2003), catalyzing the addition and removal of multiple tubulin dimers at MT plus-ends (Brouhard et al 2008), and depletion of Msps results in a dramatic increase in MT pausing with little or no growth (Brittle and Ohkura 2005).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…They belong to a subfamily of MAPs known as plus-end tracking proteins (+TIPs) (Carvalho et al, 2003) that bind microtubules and transiently accumulate at their growing plus-ends (Akhmanova et al, 2001;Sousa et al, 2007). They also localize to kinetochores of mitotic chromosomes, centrosomes, the central spindle region and the midbody (Lemos et al, 2000;Maiato et al, 2003a;Pereira et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…They also localize to kinetochores of mitotic chromosomes, centrosomes, the central spindle region and the midbody (Lemos et al, 2000;Maiato et al, 2003a;Pereira et al, 2006). Recently, it was shown that in interphase Mast has a stabilizing role on microtubules by promoting the pause state (Sousa et al, 2007). In mitosis, Mast was shown to be required for functional kinetochore-microtubule attachments, chromosome congression and maintenance of spindle bipolarity (Lemos et al, 2000;Maiato et al, 2002).…”
Section: Introductionmentioning
confidence: 99%